Liquidity, Profitability, and Capital Adequacy: Evidence from Indonesian Listed Banks - Perlita Sari Rette; Dhullo Afandi; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2026)
Capital Adequacy Ratio (CAR) reflects a bank’s ability to maintain financial stability and absorb risks. This study examines the effect of liquidity and profitability on CAR in banking companies listed on the Indonesia Stock Exchange during 2022–2024. Liquidity is measured by the Loan-to-Deposit Ratio (LDR), while profitability is proxied by Return on Assets (ROA). Using a quantitative approach and multiple linear regression analysis, this study analyzes 63 observations from 21 banks selected through purposive sampling. The results show that liquidity has a positive and significant effect on CAR, whereas profitability has no significant effect. Simultaneously, liquidity and profitability significantly influence CAR. These findings indicate that effective liquidity management plays a more important role in strengthening capital adequacy than profitability alone. This study provides empirical evidence and practical implications for banking management and regulators in maintaining financial stability and capital adequacy.